1、-2
2、30
原式=(2x)^2-(3y)^2-(4y)^2+(3x)^2
=13x^2-25y^2
原式=(16x^4+1)*(4x^2+1)*(1-4x^2)
=(16x^4+1)*(1-16x^4)
=1-256x^16
原式=(10-1)*(10+1)*(100+1)*(10000+1)
=(100-1)*(100+1)*(10000+1)
=(10000-1)*(10000+1)
=10^8-1
=99999999
原式=(2^2-1)*(2^2+1)*(2^4+1)*(2^8+1)*(2^16+1)+1
=(2^4-1)*(2^4+1)*(2^8+1)*(2^16+1)+1
=(2^8-1)*(2^8+1)*(2^16+1)+1
=(2^16-1)*(2^16+1)+1
=2^256-1+1
=2^256
(1)28=4×7=82-62;2012=4×503=5042-5022,
所以是神秘数;
(2)(2k+2)2-(2k)2=(2k+2-2k)(2k+2+2k)=4(2k+1),
∴由2k+2和2k构造的神秘数是4的倍数.
(3)设两个连续奇数为2k+1和2k-1,
则(2k+1)2-(2k-1)2=8k,
∴两个连续奇数的平方差不是神秘数.